FUNGISTATIC AND FUNGICIDAL ACTION OF ETHYLENE DIBROMIDE - SANCHEZ MARROQUIN, AY; MEDRANO, A (Hospital General, CD MEXICO, DF, MEX, 1976)
Three new high yielding vars of beans, Frijol Rocamex 1, 2, and 3, developed at the Expt Station of the been grown before All 3 vars are fairly resistant to the Apion pod Oficina de Estudios Especiales at Chapingo, Mexico, have been released for large
CLIN GENET
Keywords: FUNGISTATIC AND FUNGICIDAL ACTION, ETHYLENE DIBROMIDE; MULTIDISCIPLINARIA; BIOLOGIA VEGETAL; BOTANICA GENERAL